Políticas públicas educacionais questões e desafios contemporâneos - Brandão, Carlos da Fonseca (Editora Oficina Universitária, 2020)
If we can say that Educational Public Policies mirror a set of intentions and arenas on various aspects of Education, and I believe that we can not only as monitors, this collection brings together a group of analysts who were in charge of questioning and contrasting, with a consistent documental and legal support, clearly explaining an almost always denied link between the policy process and the legislative process. Thus, we find in this collection a very well-designed bond of the policy analyst, when one understands implicitly and explicitly, the notion that public policy and also educational policy is the State in action. This idea emerges at all times in a recurrent way, explaining the links that exist between State and Society, fundamentally when the concept of government crosses these interrelationships. If there were no others, these reasons would be enough for us to look carefully at all the chapters that make up this collective work.